Gender Inequalities in Noncommunicable Disease Risk Factors Among Indonesian Urban Population. (March 2016) - Christiani, Yodi; Byles, Julie E.; Tavener, Meredith; Dugdale, Paul
Gender is an important determinant of health. We conducted a study to examine hypertension, obesity, hypercholesterolemia, and smoking behavior among adults aged >15 years in urban Indonesia. We compared the prevalence, predicted socioeconomic factors, the gender inequalities, and the contributing factors to the inequalities. Women had a higher risk of obesity and hypercholesterolemia and raised blood pressure in later life ( P < .001). In contrast, men had a higher risk of being a current smoker and raised blood pressure at younger age ( P < .001). The gender inequalities in hypertension, obesity, and hypercholesterolemia can be accounted for by disparities in socioeconomic factors between men and women, particularly involvement in paid work. However, the inequalities were also accounted for by different effects of the socioeconomic factors in men and women. Gender is interlinked with socioeconomic and biological factors in determining health. This emphasizes the need of gender responsive policies to control and prevent chronic disease.